Effects of Low Penicillin Concentrations on Cell Morphology and on Peptidoglycan and Protein Synthesis in a Tolerant Streptococcus Strain - Mychajlonka, Myron (1981)
Rates of protein and peptidoglycan synthesis were determined by pulse-labeling techniques before and after treatment of exponentially growing cultures of Streptococcus mutans FA-1 with a number of concentrations of penicillin G (0.05, 0.1, 0.3, and 0.4 μg/ml). These penicillin concentrations were all less than that required to saturate the specific penicillin-binding sites present on the surface of this organism (0.5 μg/ml), but were all greater than and, in fact, were multiples of the minimum inhibitory concentration (0.02 μg/ml). Low concentrations of penicillin G (2.5× the minimum inhibitory concentration) immediately halted the exponential increase in the rate of peptidoglycan synthesis normally expected as the result of cell multiplication, but allowed the rate of peptidoglycan synthesis occurring at the time of penicillin addition to be maintained for almost 1 h. An increased penicillin concentration (5× the minimum inhibitory concentration) allowed the rate of peptidoglycan synthesis occurring at the time of penicillin addition to be maintained for a shorter length of time (~0.67 h). Still greater penicillin concentrations caused an immediate inhibition of the peptidoglycan synthetic rate. The effect of penicillin on the rate of protein synthesis was similar, although less pronounced. Samples were taken for scanning electron microscopy immediately before and after 3 h of treatment with a low (2.5× the minimum inhibitory concentration) concentration of penicillin. The surface areas and volumes of the cells in these samples were calculated from the electron micrographs by using computer reconstruction techniques. From the frequency distributions of surface area, the plots of surface area to volume ratio as a function of surface area, and the pulse-labeling data mentioned previously, low, growth-inhibitory concentrations (2.5× the minimum inhibitory concentration) of penicillin are proposed (i) to inhibit the constriction of the division septum, (ii) to prevent the establishment or maturation of new envelope growth sites, and (iii) to have no immediate effects on the synthesis of cell wall peptidoglycan already in progress at the time of penicillin addition.